2014
DOI: 10.1088/0004-637x/787/1/62
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence of Parsec-Scale Jets in Low-Luminosity Active Galactic Nuclei

Abstract: The nuclear radio emission of low-luminosity active galactic nuclei (LLAGN) is often associated with unresolved cores. In this paper we show that most LLAGN present extended jet radio emission when observed with sufficient angular resolution and sensitivity. They are thus able to power, at least, parsec-scale radio jets. To increase the detection rate of jets in LLAGN, we analyze subarcsecond resolution data of three low-ionization nuclear emission regions. This yields the detection of extended jet-like radio … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
49
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 95 publications
10
49
0
1
Order By: Relevance
“…in M51 Rampadarath et al in prep; more generally in Nagar et al 2002Nagar et al , 2005Panessa & Giroletti 2013;Mezcua & Prieto 2014). In NGC 660, the central source detected by e-MERLIN is both compact and flat spectrum, and the EVN map shows evidence of a core-jet structure.…”
Section: A New Period Of Agn Activitymentioning
confidence: 91%
“…in M51 Rampadarath et al in prep; more generally in Nagar et al 2002Nagar et al , 2005Panessa & Giroletti 2013;Mezcua & Prieto 2014). In NGC 660, the central source detected by e-MERLIN is both compact and flat spectrum, and the EVN map shows evidence of a core-jet structure.…”
Section: A New Period Of Agn Activitymentioning
confidence: 91%
“…Recently, Mezcua & Prieto (2014) presented measurements of luminosities of a much smaller sample of AGN, but with sufficiently larger angular resolution and sensitivity. Their estimations for L bol are more reliable than those presented in Russell et al (2013), because they measure L bol after integrating the radio to X-ray Spectral Energy Distribution (SED).…”
Section: Agn Feedbackmentioning
confidence: 99%
“…There is evidence for two distinct phases of AGN activity and feedback: the radio-mode and the quasar-mode. The radio-mode is characterized by large radio jets generating hot X-ray cavi-E-mail: steinborn@usm.lmu.de ties (Russell et al 2013, Mezcua & Prieto 2014, whereas in the quasar-mode the emission is dominated by the accretion disc, which is visible as the so-called blue bump in the spectrum of quasars and Seyfert galaxies (e.g. Elvis et al 1994, Prieto et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies aiming at comparing the radiative and kinetic properties have been recently performed (e.g., King et al 2012;Mezcua & Prieto 2014;Hlavacek-Larrondo et al 2015;Hogan et al 2015;Shin et al 2016) In this work, we mainly use results by Russell et al (2013), one of the most comprehensive investigations based on observations of nuclear X-ray sources and the corresponding cavities in a large sample of 57 BCGs. These authors have found that the nuclear radiation exceeds the mechanical energy output of the outflow when the mean accretion rate rises above a few percent of the Eddington luminosity, corresponding to the onset of the quasar mode.…”
Section: Observational Constraintsmentioning
confidence: 99%